Evaluation Of Functionality And Usability For Smart Card Issuance System - Mohd Noorulfakhri, Yaacob (2008)
One of the ways to evaluate a smart card issuance system's functional qualities and usability is by evaluating it based on measurements that have been defined for each criterion. A smart card issuance system is a system that will produce smart cards for the students in local universities. Although this system has been used widely in the local universities, there are a number of complaints from the users about the functionality and usability of the system. The functionality and usability of the smart card issuance system is one of the key features of its success. This study aims to evaluate this system on its functionality and usability. The measures for evaluating its functionality and usability are defined in this study. It is hoped that by conducting the research for evaluating this smart card issuance system, it will provide the solution and suggestion on ways and methods to enhance the quality of the system itself.